Kondisi Pengusaha Indonesia Ditengah Pandemi Covid-19: Work From Home Dan Strategi Survive - Ilham, IIham (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2020)
The policy of social distancing enforcement to social restrictions (PSBB) is a step traveled by the government as an effort to prevent the spread of Corona Virus Disease (Covid-19) in Indonesia. The call to work from home is then socialized in the community, as the hashtag in the form of an invitation to remain #Dirumahsaja become viral on various social media. The birth of this policy then affect the economic sector that ultimately make the business world to be involved. So in this study will study about the condition of young Indonesian businessmen as well as survive strategy in the middle of the pandemic Covid-19, as for methods used through a qualitative descriptive approach. For informant taken from the young entrepreneurs who are in 30 cities scattered in the region of Indonesia. Data analysis is conducted through three phases of activity; Data reduction ; presentation of data (display data), and Withdrawal of conclusion (verification). In order to obtain data to answer research questions and research purposes, the techniques used are interviews, documentation and literature study. The results of this study showed that the impact of the Covid-19 pandemic against Indonesian young entrepreneurs varies; Still survive, depressed to close the business, switch to open a new business, and develop in the middle of the Covid-19 pandemic. Those who are able to survive and thrive are mostly businesses that run online, primarily the utilization of social media (sosmed) as a means of promotion of products. The strategy of young Indonesian entrepreneurs who successfully summarized to remain survive in the midst of the Covid-19 pandemic, among them; (1) to build a digital marketing channel, (2) maximize the utilization of social media as promotional means, (3) to build networking, (4) Provide good service, (5) Maintain product quality and ensure stay safe from Covid-19, (6) provide discounts to consumers such as free shipping, (7) switching focus by opening the relevant business, and (8) Create a new business plan after the Covid-19 pandemic.